A case of intentional lateralization of the tympanic membrane for surgical treatment of glomus jugulare tumor with pulsatile tinnitus via transcanal endoscopic ear surgery - FUKAHORI, Mioko; TANAKA, Hisaichiro; CHITOSE, Shun-ichi; UMENO, Hirohito; SATO, Kiminobu; MIHASHI, Ryota; ONO, Takeharu; KUROIWA, Taikai; KAWAGUCHI, Toshihiko (jibi to rinsho, 2023)
Complete resection of glomus jugulare tumor (GJT) may result in postoperative inferior cranial nerve palsy. Therefore, a wait-and-scan policy is often chosen in elderly patients. Patients may suffer from pulsatile tinnitus for a long period of time. We performed intentional lateralization of the tympanic membrane for a GJT with pulsatile tinnitus. Case: A 67-year-old woman had had pulsatile tinnitus for 3 years. A reddish pulsatile mass was detected in the lower quadrant of the right tympanic membrane. The diagnosis of GJT (Fisch classification: Class C2) was made based on an imaging examination. Since there was no evidence of inferior cranial nerve palsy, a wait-and-scan approach was selected. However, pulsatile tinnitus caused insomnia and worsening depression. After obtaining her informed consent, we performed intentional lateralization of the tympanic membrane via transcanal endoscopic ear surgery. Immediately after the surgery, the pulsatile tinnitus disappeared. Intentional lateralization of the tympanic membrane may be a treatment option for GJT with pulsatile tinnitus.